Attitudes about Future Genetic Testing for Posttraumatic Stress Disorder and Addiction among Community-Based Veterans - Lent, Michelle R.; Hoffman, Stuart N.; Kirchner, H. Lester; Urosevich, Thomas G.; Boscarino, Joseph J.; Boscarino, Joseph A. (Frontiers in Psychiatry, 2017)
This study explored attitudes toward hypothetical genetic testing for posttraumatic stress disorder (PTSD) and addiction among veterans. We surveyed a random sample of community-based veterans (n=700) by telephone. One year later, we asked the veterans to provide a DNA sample for analysis and 41.9% of them returned the DNA samples. Overall, most veterans were not interested in genetic testing neither for PTSD (62%) nor for addiction (69%). However, bivariate analyses suggested there was an association between having the condition of interest and the likelihood of genetic testing on a 5-point scale (p<0.001 for PTSD; p=0.001, for alcohol dependence). While ordinal regressions confirmed these associations, the models with the best statistical fit were bivariate models of whether the veteran would likely test or not. Using logistic regressions, significant predictors for PTSD testing were receiving recent mental health treatment, history of a concussion, younger age, having PTSD, having alcohol dependence, currently taking opioids for pain, and returning the DNA sample during the follow-up. For addiction testing, significant predictors were history of concussion, younger age, being on psychotropic medications, having alcohol dependence, and currently taking opioids for pain. Altogether, 25.9% of veterans reported that they would have liked to have known their genetic results before deployment,15.6% reported after deployment, and 58.6% reported they did not want to know neither before nor after deployment. As advancements in genetic testing continue to evolve, our study suggests that consumer attitudes toward genetic testing for mental disorders are complex and better understanding of these attitudes and beliefs will be crucial to successfully promote utilization.